2009
DOI: 10.1016/j.jcv.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Human rhinovirus C associated with wheezing in hospitalised children in the Middle East

Abstract: Background-Few studies have investigated the disease burden and genetic diversity of human rhinoviruses (HRV) in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
139
5
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(170 citation statements)
references
References 40 publications
25
139
5
1
Order By: Relevance
“…Previously, we have shown that HRV-C is the most common virus detected in children with acute asthma exacerbations and is associated with more severe episodes compared with other viruses (23). Yet, other studies have found variable results on HRV in young children with ARIs (21,(26)(27)(28)(29)(30). This could be due to the inclusion of milder cases, as HRV-C appears to be most common in children with more severe wheezing exacerbations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previously, we have shown that HRV-C is the most common virus detected in children with acute asthma exacerbations and is associated with more severe episodes compared with other viruses (23). Yet, other studies have found variable results on HRV in young children with ARIs (21,(26)(27)(28)(29)(30). This could be due to the inclusion of milder cases, as HRV-C appears to be most common in children with more severe wheezing exacerbations.…”
Section: Discussionmentioning
confidence: 90%
“…A number of studies have shown that HRV-C is the most common HRV species associated with acute asthma attacks severe enough to result in children presenting to hospital (18)(19)(20)(21), and further studies have shown that it also causes more severe asthma attacks than other rhinoviruses (22) and all other viruses (23).…”
mentioning
confidence: 99%
“…Since then, multiple studies have compared the virulence of HRV-C relative to the classical HRV-A and -B species (13,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). In several of these studies, HRV-C viruses appear to be overrepresented compared with HRV-A and -B in infants and children with lower respiratory infections and in exacerbations of childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
“…13 Asimismo, se ha hallado la presencia de RVH en pacientes con bronquiolitis, 14 neumonía, 15 EPOC, 16 fibrosis quís-tica 17 y pacientes inmunocomprometidos, tanto en niños como en adultos. Miller y col., 18 demostraron que la historia familiar de atopía, especialmente en la madre, fue un factor de riesgo para presentar bronquiolitis grave en 630 niños pequeños hospitalizados y ambulatorios.…”
Section: Discussionunclassified